Cutaneous rosacea: a thorough overview of pathogenesis, clinical presentations, and current recommendations on management - JAMES Q. Del Rosso (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The review summarizes and systemizes available international data on the pathogenesis, clinical manifestations and current recommendations for the management of rosacea patients.